2021
DOI: 10.1080/08957959.2021.1961765
|View full text |Cite
|
Sign up to set email alerts
|

Equations of state of new boron-rich selenides B6Se and B12Se

Abstract: Two novel of boron-rich selenides, orthorhombic B6Se and rhombohedral B12Se, have been recently synthesized at high pressurehigh temperature conditions. Room-temperature compressibilities of these phases were studied in a diamond anvil cell using synchrotron powder X-ray diffraction. A fit of experimental p-V data by third-order Birch-Murnaghan equation of state yielded the bulk moduli of 155(2) GPa for B12Se and 144(3) GPa for B6Se. No pressure-induced phase transitions have been observed in the studied press… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Boron (B)-rich compounds having structural units of B 12 closed cage clusters are novel systems attracting significant interest of the research community. Many interesting physical properties such as high hardness, useful electronic properties, low mass density, a very high melting point, and excellent thermal stability and chemical inertness of B-rich compounds have gained extra attention of the materials science and engineering research community in view of the potential technical applications. , Among the B-rich compounds, the B-rich solids with icosahedral clusters ,, structurally derived from α-rhombohedral boron (α-rh boron) offer some industrial potential candidate materials similar to boron carbide, boron sub-oxide and boron sub-phosphide, REB 15.5 CN, REB 22 C 2 N, and REB 28.5 C 4 (RE = heavy rare-earth element, Y, and Sc). Recent discovery of B-rich compounds has received considerable research attention for the betterment of the physical properties in these days. ,, Very recently, Cherednichenko et al have synthesized 3D B-rich compounds B 12 S and B 12 Se using a chemical reaction process at a pressure of 6 GPa and a temperature of 2500 K. With the help of powder X-ray diffraction and Raman spectroscopy, it is found that the crystal structure belongs to rhombohedral symmetry with the space group R 3̅ m (no. 166).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boron (B)-rich compounds having structural units of B 12 closed cage clusters are novel systems attracting significant interest of the research community. Many interesting physical properties such as high hardness, useful electronic properties, low mass density, a very high melting point, and excellent thermal stability and chemical inertness of B-rich compounds have gained extra attention of the materials science and engineering research community in view of the potential technical applications. , Among the B-rich compounds, the B-rich solids with icosahedral clusters ,, structurally derived from α-rhombohedral boron (α-rh boron) offer some industrial potential candidate materials similar to boron carbide, boron sub-oxide and boron sub-phosphide, REB 15.5 CN, REB 22 C 2 N, and REB 28.5 C 4 (RE = heavy rare-earth element, Y, and Sc). Recent discovery of B-rich compounds has received considerable research attention for the betterment of the physical properties in these days. ,, Very recently, Cherednichenko et al have synthesized 3D B-rich compounds B 12 S and B 12 Se using a chemical reaction process at a pressure of 6 GPa and a temperature of 2500 K. With the help of powder X-ray diffraction and Raman spectroscopy, it is found that the crystal structure belongs to rhombohedral symmetry with the space group R 3̅ m (no. 166).…”
Section: Introductionmentioning
confidence: 99%
“…The stoichiometric ratio of the chalcogenides has been computed. Furthermore, only the bulk modulus of B 12 Se among all mechanical properties has been studied using the third-order Birch–Murnaghan equation of state so far . In 2021, Solozhenko , measured the microhardness of 3D B-rich compounds B 12 S and B 12 Se experimentally using Vicker hardness ( H V ) and Knoop hardness ( H K ) methods and also studied the oxidation resistance by thermal analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wave functions were expanded in a plane-wave basis set with a cut-off energy of 720 eV with k-point sampling inside the first Brillouin zone constructed using the a, b Theoretical value of C ij and Bulk modulus [24,26]. c Experimental Bulk modulus [25].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The Raman spectra, at atmospheric pressure, show bands from 150 to 1110 cm −1 . Cherednichenko also presented theoretical calculations on the crystal structure of the B 6 Se chalcogenide in the interval from zero to 35 GPa; estimating a bulk modulus (B 0 ) of 144 GPa at zero GPa [25] and suggesting the possibility of being a high hardness material. Subsequently, Hossain and co-workers [26] reported a comprehensive theoretical study of the mechanical and physical properties of both B 6 Se and B 6 S chalcogenides, at zero GPa.…”
Section: Introductionmentioning
confidence: 99%